Population Density of Thalassina scorpionides (Rama-Rama) in the Reuleung River Mangrove Ecosystem, Leupung, Aceh Besar - Zulfikar Zulfikar; M. Ali Sarong; Mimie Saputri (Universitas Syiah Kuala, 2019)
Thalassina scorpionides (Rama-Rama) belong to the Thalassina genus and act as a detritivor. However, information on the density of T. scorpionides based on domestic and overseas literature is still low therefore research needs to be done on population density of T. scorpionides in Mangrove Ecosystem of Reuleung River Leupung District of Aceh Besar Regency. The research was conducted in July 2017. The purpose of this study was to determine the population density of T. scorpionides. Data obtained through survey method with purposive sampling technique. The sampling location is divided into 5 stations and each station has 3 plots. Population density analysis using population density formula. The result showed that population density of T. scorpionides at station I was 3 ind / m2, station II 1 ind / m2, station III 1 ind / m2, station IV 1 ind / m2, and station V 2 ind / m2. Population density of T. scorpionides is most common in station I and the lowest population density is found in station III. Abiotic factor at location of observation station of T. scorpionides that is temperature of water ranged from 25oC-31oC, air temperature 25oC-33oC, salinity of 17 ‰ -22 ‰, and soil pH ranged from 5-7.2, water pH ranged from 5-7.4 and substrate in the form of sandy clay soils, fine pebbles, sludge mud, gravel, and muddy.